Toward improved immunocompetence of adoptively transferred CD8(+) T cells - Speiser, Daniel E. (American Society for Clinical Investigation, 2005)
Adoptive transfer of autologous or allogenic T cells to patients is being used with increased frequency as a therapy for infectious diseases and cancer. However, many questions remain with regard to defining optimized procedures for preparation and selection of T cell populations for transfer. In a new study in this issue of the JCI, Gattinoni and colleagues used a TCR transgenic mouse model to examine in vitro–generated tumor antigen–specific CD8(+) T cells at various stages of differentiation for their efficacy in adoptive immunotherapy against transplantable melanoma. The results confirm that CD8(+) T cells progressively lose immunocompetence with prolonged in vitro cultivation and suggest that effector CD8(+) T cells alone may be considerably less potent at protecting hosts with advanced tumors than are less differentiated T cells.